Pemetaan Konflik Manusia dengan Orangutan Sumatera (Pongo abelii Lesson 1827) Berdasarkan Informasi Masyarakat di Desa Peunaron Lama, Kabupaten Aceh Timur, Indonesia - Siti Munta Siroh; Khairil Khairil; Asiah MD; Yuri Gagarin; Zulfikar Zulfikar; Cut Nurmaliah; Rusnawati Rusnawati; Abdullah Abdullah (Jurnal Penelitian Pendidikan IPA, 2023)
The Sumatran orangutan is a species of great ape originating from the island of Sumatra and is currently endangered. The survival of the Sumatran orangutan is threatened due to forest conversion to plantations, illegal logging and habitat fragmentation which causes conflict with humans. Until now there is still a lack of scientific information about the mapping of human-orangutan conflicts. In an effort to preserve and protect animals, it is necessary to do a mapping to map the problems that exist in the field. This study aims to carry out mapping to find out the map of the path of human conflict with the Sumatran Orangutan. The method used in this study is field observation and interviews with a qualitative descriptive approach. Data is presented in the form of tables and figures descriptively. The results of this study found a map of orangutan conflict routes which included: residential areas, plantations, secondary forests and primary forest areas. Each of these areas consists of 2 points of conflict path.